5(x-2)=4(x-3)

Simple and best practice solution for 5(x-2)=4(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-2)=4(x-3) equation:


Simplifying
5(x + -2) = 4(x + -3)

Reorder the terms:
5(-2 + x) = 4(x + -3)
(-2 * 5 + x * 5) = 4(x + -3)
(-10 + 5x) = 4(x + -3)

Reorder the terms:
-10 + 5x = 4(-3 + x)
-10 + 5x = (-3 * 4 + x * 4)
-10 + 5x = (-12 + 4x)

Solving
-10 + 5x = -12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-10 + 5x + -4x = -12 + 4x + -4x

Combine like terms: 5x + -4x = 1x
-10 + 1x = -12 + 4x + -4x

Combine like terms: 4x + -4x = 0
-10 + 1x = -12 + 0
-10 + 1x = -12

Add '10' to each side of the equation.
-10 + 10 + 1x = -12 + 10

Combine like terms: -10 + 10 = 0
0 + 1x = -12 + 10
1x = -12 + 10

Combine like terms: -12 + 10 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| 1-x=x-1 | | 5-x=x-4 | | 3-5x=4x-6 | | 2*c+6*c+8=32 | | 2x-4=11-x | | 6x-4-2x=4 | | 9*y-5*y=8 | | 9-6x=2x+25 | | 2-5x=x-1 | | 3-4x=x-7 | | 6x^23+20=0 | | 4(3x+5)=5(2x+3) | | 32=13-4*x+21 | | 6w-15=9qw | | 4(x*5)+2=x+3 | | 5x-2=14-x | | 5x^2+34x+24=0 | | (13+x)+(9+x)=(73+x) | | x+17=39 | | 122-4x=32x+22 | | 9-8x=73-22x | | -130-7x=10x+23 | | 5x+7=-53-7x | | -4=8+6p | | =8wx*4w | | 5x+4=2x+6 | | 7x-3=5x+4 | | 96=x+(x*2)+2*(x*2) | | x^2+9x-16=0 | | 3x-8=5x+4 | | 6(2x-3)=42 | | 4Y+16=0 |

Equations solver categories